Determination of error level of ultrasonographic fetal weight estimation according to the seniority of residents in obstetrics and gynecology - Çift, Tayfur; Temür, Muzaffer; Yıldızbakan, Mehtap; Türker, Ayşe Ülkü; Öztaş, Sonay; Acar, Yeliz; Üstünel, Sibel; Üstünyurt, Emin (The European Research Journal, 2020)
Objectives: We consider the difference between estimated fetal weight and birth weight through the measurement according to the seniority of the residents in obstetrics and gynecology. In this study, we aimed to determine the fallibility of the residents according to their seniority years. Methods: This research was planned as a prospective and approved by the Ethics Committee Ultrasonographic measurements were performed with ultrasound device and the estimated fetal weight was calculated with Hadlock 4 (BPD, HC, AC, FL) formula. Measurements were performed by the residents in the first, second, third and fourth year of training and repeated by the same specialist for each patient. Only those who gave birth within 48 hours of the ultrasonographic measurements were included in the study. Results: A total of 392 pregnant women were included in the study. Ninety-eight pregnant women were examined by 1st year resident, 100 pregnant by 2nd year resident, 93 pregnant by 3rd year resident and 101 pregnant by 4th resident. Largest difference between the estimated fetal weight and birth weight was performed by the fourth year resident with 125.06 ± 247.40 grams. Conclusions: The estimated fetal weight by ultrasonography has an important place in obstetric practice and it may vary according to the years of seniority of the resident. For this reason, ultrasonography should be used effectively and accurately during the training of the residents in the centers of education in obstetrics and gynecology and it is essential that the residents learn the ultrasound examination properly and completely.